2018
DOI: 10.1093/rpd/ncy101
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive Disequilibrium and Dynamic of Natural Radionuclides in Soils in the State of Pernambuco—brazil

Abstract: Environmental radioactivity studies have been allowed establishing radiometric patterns in several area of the earth's crust. The work was conducted through radiometric analyses of regions with high levels of radionuclides and others with no history of anomalies. The research allowed establishing the radiometric profile of soils in the state of Pernambuco, Brazil, using a gamma spectrometry system. The specific activities ranged from 16.5 to 287.5 Bq kg-1 for 238U, 2.0 to 191.7 Bq kg-1 for 226Ra, 1.3 to 281.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Additionally, the lithosphere naturally contains three times as much thorium as uranium or radium [40]. Each location in the world has different geological and topographical conditions, which affect radioactivity in soils [41][42][43]. Variations in soil activity levels can be attributed to factors such as the soil-to-water ratio, the rate and amount of rainfall, soil drainage, site characteristics, and other environmental variables like meteorological conditions, soil use patterns, fertilizer use, evaporation, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the lithosphere naturally contains three times as much thorium as uranium or radium [40]. Each location in the world has different geological and topographical conditions, which affect radioactivity in soils [41][42][43]. Variations in soil activity levels can be attributed to factors such as the soil-to-water ratio, the rate and amount of rainfall, soil drainage, site characteristics, and other environmental variables like meteorological conditions, soil use patterns, fertilizer use, evaporation, etc.…”
Section: Resultsmentioning
confidence: 99%
“…The values of the gamma index were ranged from 0.2139 to 0.3629. It's observed that each one sample has gamma index Iγ<1 which suggests gamma dose rate emission from these samples was not exceeding 0.3 mSv/y [25]. The calculated values of H ex were found to vary from 0.0794 to 0.1368, with a mean value of 0.1094.…”
Section: Radiological Health Risk Assessmentmentioning
confidence: 92%
“…The specific activities of 226 Ra radionuclides were calculated by applying Equation 3 (Santos Júnior et al, 2018):…”
Section: Eq(2)mentioning
confidence: 99%
“…The 212 Pb (half-lives (t1 / 2) short 10.64 hours), 211 Pb (half-lives (t1 / 2) short 36.1 minutes), and 214 Pb (half-lives (t1 / 2) short 26, 8 minutes) and therefore they do not migrate to great distances in the environment. On the other hand, 210 Pb with a half-life of 22.26 years was found in many environmental samples (Santos Júnior et al, 2018). 210 Pb can be found adsorbed to atmospheric particles and can return to the soil by the action of rain, in which they can form compounds and rapidly distributed in the environment (Silva et al, 2018).…”
Section: Introductionmentioning
confidence: 99%